PARENTS’ DIGITAL COPING RESOURCES WITH ONGOING POLITICAL CONFLICTS - Yeshua-Katz, Daphna; Shapira, Stav; Braun-Lewensohn, Orna (AoIR Selected Papers of Internet Research, 2023)
Mobile technologies such as the instant messaging application WhatsApp have become significant resources for information and social support in times of crisis, as well as for crisis communication. In times of crisis, these applications afford the exchange of real-time information and can influence users' coping behaviors. Conversely, they have also been reported to constitute a potential source of misinformation and increased exposure to emotional distress. To date, the role WhatsApp groups play for individuals, families, and communities living in regions affected by ongoing conflicts has yet to be investigated.This research draws upon the salutogenic and ecological theories to examine parents' digital coping processes with political violence in southern Israel. To this end, the study examines the types of coping resources provided in local online parent groups (OPGs) during violence escalation and relative calm periods. The study involves a mixed-methods approach comprising qualitative in-depth interviews with 15 couples who are parents of children under the age of 17 residing in communities near the Israel-Gaza border and an online ethnography of four local OPGs. Study findings reveal three levels of parents' coping resources on OPGs: personal, family, and communal digital coping resources. In addition, four WhatsApp affordances immediacy, reachability, mobility, and multimediality—contributed to WhatsApp's role as a shared and ubiquitous coping resource. This study expands the original models and core concepts of the salutogenic and ecological paradigms traditionally studied solely in offline environments and examines the effectiveness of digital contexts in helping parents cope with an ongoing collective stressor.